Privacy policies and practices: an investigation of secondary use of information within South African retail banking institutions - Daya, Jithendra Chotoo (My University, 1996)
This paper addresses concerns surrounding information privacy and the secondary use of information in South African corporations. This study also attempts to assess the level of concern that management and information technology practitioners if! South African retail banks have about privacy issues. The research suggests that privacy is a huge concern internationally and may affect South African corporations if they do not follow certain policies and practices. Eleven in-person structured interviews were conducted at four banks. The research proposes a set of guidelines by which South African management and IT practitioners, who are involved with the identification and solution of some of the problems that may be presented by possible privacy legislation, will be able to assess their policies and practices against international practices and policies. The results inform IS managers and executives about appropriate business policies they can implement voluntarily to address public concerns about specific information practices that may be considered a threat to privacy. The findings suggest that the executives are deliberately avoiding confronting the issue of information privacy for as long as possible. The executives are adopting a wait-and-see attitude and will react 011 whatever legislation requires them to do. At the time of the report senior executives at banks were not accepting responsibility for information privacy policies and practices and were leaving this responsibility; to the middle level managers who implement their own practices based on their own needs.
A research report submitted to the Faculty of Commerce, University of the Witwatersrand, Johannesburg, in the partial fulfilment of the requirements for the degree of Master of Commerce. Johannesburg 1996.
Keywords: Privacy, Right of; Electronic data processing departments--Secutity measures; Information technology--Social aspects; Banks and banking--South Africa